Carrying the Cross : The Autobiography of Bishop Matthew Oluremi Owadayo - Owadayo, Matthew Oluremi (Book collections on Project MUSE., 2014)
Born in Ifira-Akoko, Nigeria in 1939 Bishop Matthew Oluremi Owadayo was appointed Menís warden of Archbishop Vining Training Centre, Akure; preferred Cathedral Provost, and later Dean, Immanuel College of Theology, Ibadan. In December 1994, he was elected Bishop of the Diocese of Egba.